Left prefrontal high-frequency repetitive transcranial magnetic stimulation for the treatment of schizophrenia with predominant negative symptoms: a sham-controlled, randomized multicenter trial - Wobrock, Thomas; Rietschel, Marcella (Biological psychiatry, 2015)
Investigators are urgently searching for options to treat negative symptoms in schizophrenia because these symptoms are disabling and do not respond adequately to antipsychotic or psychosocial treatment. Meta-analyses based on small proof-of-principle trials suggest efficacy of repetitive transcranial magnetic stimulation (rTMS) for the treatment of negative symptoms and call for adequately powered multicenter trials. This study evaluated the efficacy of 10-Hz rTMS applied to the left dorsolateral prefrontal cortex for the treatment of predominant negative symptoms in schizophrenia. A multicenter randomized, sham-controlled, rater-blinded and patient-blinded trial was conducted from 2007-2011. Investigators randomly assigned 175 patients with schizophrenia with predominant negative symptoms and a high-degree of illness severity into two treatment groups. After a 2-week pretreatment phase, 76 patients were treated with 10-Hz rTMS applied 5 days per week for 3 weeks to the left dorsolateral prefrontal cortex (added to the ongoing treatment), and 81 patients were subjected to sham rTMS applied similarly. There was no statistically significant difference in improvement in negative symptoms between the two groups at day 21 (p = .53, effect size = .09) or subsequently through day 105. Also, symptoms of depression and cognitive function showed no differences in change between groups. There was a small, but statistically significant, improvement in positive symptoms in the active rTMS group (p = .047, effect size = .30), limited to day 21. Application of active 10-Hz rTMS to the left dorsolateral prefrontal cortex was well tolerated but was not superior compared with sham rTMS in improving negative symptoms; this is in contrast to findings from three meta-analyses.